COMMUNICATION STRATEGY OF PENGELOLA KAWASAN KONSERVASI PERAIRAN DAERAH (KKPD) WITH COMMUNITY TO CONSERVE CORAL REEFS IN MALANG RAPAT VILLAGE OF GUNUNG KIJANG DISTRICT OF BINTAN REGENCY OF RIAU ISLAND PROVINCE - Ranti Rumapea; Zulkarnain Umar; Kusai Yatim (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted in January in Malang Rapat Village of Gunung Kijang District of Bintan Regency of Riau Island Province. This study aims to determine the techniques of KKPD managers in conserving Coral Reefs, knowing communication strategies used KKPD managers with communities in conserving Coral Reefs and knowing the success rate of KKPD managers in conserving Coral Reefs. The method used in this research is qualitative research method.The types of communication strategies used by the managers of the Regional Aquatic Conservation Area with communities in conserving the Coral Reefs are identifying target communities, setting communication goals, designing messages, socializing, creating advertisements, creating good relationships with communities. Keywords: Communication Strategy, Coral Reef, Malang Village Meeting